The impact of Preferential Trade Agreements on the economy : NAFTA case - Simonyan, Lev (2018)
The current paper is designed to examine the possible impact of preferential trade agreements (PTA) on the economy of the country involved. The topic is extremely important due to the increased number of various PTAs all over the world and decreased the pace of multilateral trade liberalization. Moreover, the recent issue with NAFTA agreement, which is in danger of being terminated and which also served as practical evidence for the paper, also contributed to the significance of the topic. The comprehensive analysis of theoretical literature as well as analysis of the statistical data related to the economic development of the US since 1994 was conducted to examine the significance of PTAs. It was found out that PTAs rarely can negatively impact the countries involved. Moreover, it was proved that NAFTA benefited to the economy of the US as well as to the integration of region significantly. Therefore, NAFTA should stay, and the PTAs seem to be the most relevant tool of trade liberalization nowadays.